Carprofen provides better post-operative analgesia than tramadol in dogs after enucleation: A randomized, masked clinical trial - Delgado, Cherlene (J Am Vet Med Assoc, 2014)
OBJECTIVE: To compare analgesia provided by carprofen or tramadol in dogs after enucleation. DESIGN: Randomized, masked trial ANIMALS: Forty-three dogs PROCEDURES: Client-owned dogs admitted for routine enucleation were randomly assigned to receive either carprofen or tramadol orally 2 hours prior to surgery and 12 hours after the first dose. Dogs were scored for pain at baseline, and postoperatively at 0.25, 0.5, 1, 2, 4, 6, 8, 24, and 30 hours after extubation. Dogs received identical premedication and inhalation anesthesia regimens, including premedication with hydromorphone. If the total pain score was ≥9, if there was a score ≥ 3 in any one category, or if the visual analog scale score (VAS) was ≥35 combined with a palpation score of >0, rescue analgesia (hydromorphone) was administered and treatment failure was recorded. Characteristics between groups were compared with a Student’s t-test and Fisher’s exact test. The incidence of rescue was compared between groups using a log rank test. Pain scores and VAS scores between groups were compared using repeated measures ANOVA. RESULTS: There was no difference in age (p=0.493), gender (p=0.366) or baseline pain scores (p=0.288) between groups. Significantly more dogs receiving tramadol required rescue analgesia (6/21) compared to dogs receiving carprofen (1/22; p=0.035). Pain and VAS scores decreased linearly over time (p=0.038, p<0.001, respectively). There were no significant differences in pain (p=0.915) or VAS scores (p=0.372) between groups at any time point (dogs were excluded from analysis after rescue). CONCLUSIONS AND CLINICAL RELEVANCE: This study suggests that carprofen, with opioid premedication, provides more effective post-operative analgesia than tramadol in dogs undergoing enucleation.